Omentin-1, a Novel Adipokine, Is Decreased in Overweight Insulin-Resistant Women With Polycystic Ovary Syndrome : Ex Vivo and In Vivo Regulation of Omentin-1 by Insulin and Glucose - TAN, Bee K; ADYA, Raghu; FARHATULLAH, S; LEWANDOWSKI, Kris C; O'HARE, Paul; LEHNERT, Hendrik; RANDEVA, Harpal S (Diabetes (New York, N.Y.), 2008)
Polycystic ovary syndrome (PCOS) is associated with insulin resistance and obesity. Recent studies have shown that plasma omentin-1 levels decrease with obesity. Currently, no data exist on the relative expression and regulation of omentin-1 in adipose tissue of women with PCOS. The objective of this study was to assess mRNA and protein levels of omentin-1, including circulating omentin-1, in omental adipose tissue of women with PCOS and matched control subjects. Ex vivo and in vivo regulation of adipose tissue omentin-1 was also studied. Real-time RT-PCR and Western blotting were used to assess mRNA and protein expression of omentin-1. Plasma omentin-1 was measured by enzyme-linked immunosorbent assay. The effects of d-glucose, insulin, and gonadal and adrenal steroids on adipose tissue omentin-1 were analyzed ex vivo. The in vivo effects of insulin (hyperinsulinemia) on omentin-1 levels were also assessed by a prolonged insulin-glucose infusion. In addition to decreased plasma omentin-1 levels in women with PCOS (P < 0.05), compared with control subjects, there was significantly lower levels of omentin-1 mRNA (P < 0.01) and protein (P < 0.05) in omental adipose tissue of women with PCOS (P < 0.01). Furthermore, in omental adipose tissue explants, insulin and glucose significantly dose-dependently decreased omentin-1 mRNA expression, protein levels, and secretion into conditioned media (P < 0.05, P < 0.01). Also, hyperinsulinemic induction in healthy subjects significantly reduced plasma omentin-1 levels (P < 0.01). Our novel findings reveal that omentin-1 is downregulated by insulin and glucose. These may, in part, explain the decreased omentin-1 levels observed in our overweight women with PCOS.